Immune response of vaccinated juvenile gilthead seabream (Sparus aurata) after LCDV-Sa infection - Leiva-Rebollo, Rocío; Gémez-Mata, Juan; Borrego-García, Juan José; Castro-López, María Dolores; Labella Vera, Alejandro Manuel (My University, 2022)
Lymphocystis disease is one of the main viral pathologies affecting cultured gilthead seabream in the Mediterranean area. In our group, a DNA-vaccine has been developed based on the major capsid protein (MCP) of the Lymphocystis Disease Virus 3 (LCDV-Sa). The aim of the present study is the evaluation of immune-related gene expression in vaccinated fish after viral infection to identify immunogenes involved in the vaccine-induced protection. To fulfil this objective an OpenArray® platform has been developed to study 49 genes related to the immune response. Reference and viral genes were also evaluated. Gilthead seabream specimens (5 g mean weight) were distributed into 3 experimental groups, inoculated with the vaccine at 0.1 µg/g fish dose, the empty plasmid at the same dose or PBS. Thirty days post-vaccination, fish were intramuscularly injected with the virus at 106 TCID50/fish dose. Samples of head-kidney, spleen, intestine and caudal fin from 6 fish were individually collected at 1, 2 and 3-days post-injection in all groups. The quantification of viral DNA in fins of fish challenged with LCDV-Sa were carried out by a qPCR assay targeting a viral structural gene (putative myristoylated membrane protein, MMP) alternative to the mcp gene contained in the vaccine. The results obtained showed an increase of genes deregulated within the haematopoietic organs between vaccinated and non-vaccinated fish. However, in the intestine and fin, the results showed the opposite trend. The global effect of fish vaccination was a diminished immune response compared to non-vaccinated fish, being 83 and 99 genes differentially expressed through the experiment, respectively. Moreover, viral replication decreased in groups of fish previously vaccinated. The modulation of the immune response provoked by the vaccination trial seems to control the progression of the disease.
Keywords: Vacunación de animales - Congresos; Vacunas ADN - Congresos; Doradas - Enfermedades por virus - Congresos; DNA vaccine; Immune response; LCDV infection; Gilthead seabream